Relationship between pulmonary function and physical performance among community‐living people: results from Look‐up 7+ study. Issue 1 (4th December 2019) - Landi, Francesco; Salini, Sara; Zazzara, Maria Beatrice; Martone, Anna Maria; Fabrizi, Sofia; Bianchi, Mariangela; Tosato, Matteo; Picca, Anna; Calvani, Riccardo; Marzetti, Emanuele
Abstract: Background: While respiratory muscle strength is recognized to decline with aging process, the relationship between sarcopenia and pulmonary function remains to be studied. The present study was undertaken to provide a better insight into the comprehension of the relationship between pulmonary function and muscle function (strength and physical performance) using an unselected sample of subjects assessed during the Longevity Check‐up 7+ project. Methods: Look‐up 7+ is an ongoing cross‐sectional survey started in June 2015 and conducted in unconventional settings (i.e. exhibitions, malls, and health promotion campaigns) across Italy. Candidate participants are eligible for enrolment if they are at least 18 years of age and provide written informed consent. Muscle strength was assessed by handgrip strength test, and physical performance was evaluated by chair stand test. Spirometer analysis was performed using the AirSmart system, and the largest forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), and peak expiratory flow (PEF) values were collected. Results: The mean age of 925 subjects participating in the Longevity check‐7+ surveys and receiving the spirometer evaluation was 55.6 years (range from 18 to 98 years), and 501 (54%) were women. Overall, both in male and female participants, FVC, FEV1 and PEF positively correlated with handgrip strength and chair stand tests. The receiver operator characteristic curve analysis revealed that the areas under the curves for FVC, FEV1, and PEF were 0.79, 0.80 and 0.80, respectively. Conclusions: The results clearly show that pulmonary function was positively associated with handgrip strength and chair stand tests. Based on this observation, muscle strength, physical performance, and pulmonary function should be recommended as the method of choice for the early detection of individuals at risk of probable sarcopenia and at the same time to better characterized the severity of sarcopenia status.